Ultrasound-Assisted Catalyst-free Synthesis of α,β -Unsaturated Amino Acid Esters and Unsaturated Amino Ketones - Xie, Guoshu; de Moura Ricketti, Nicolas; Török, Béla (Current Green Chemistry, 2024)
Introduction: Sonication has been introduced as a green and effective activation method for the selective monoamination of β-dicarbonyl compounds. The simple one-pot process resulted in different substituted β-amino-α,β-unsaturated esters and ketones at room temperature with quantitative yields. Aqueous NH4OH was used as a safe and economical nitrogen source for pressurized NH3gas. The process is considered green, accounting for not using any solvents and catalysts, besides some aqueous NH4OH-involved reactions using nontoxic water. A broad variety of useful synthetic intermediates, β- amino-α,β-unsaturated esters and ketones have been prepared in short reaction time. Methods: Using this developed protocol, we were able to synthesize a series of structurally diverse β- amino-α,β-unsaturated esters and unsaturated amino ketones. Results: The synthesis of target compounds was achieved in a truly green process with high atom economy and excellent yields in a catalyst-free one-pot system in an aqueous medium using simple, commercially available, inexpensive ammonium hydroxide as the source of the nitrogen. The high atom economy has been accompanied by the formation of a small amount of nontoxic waste, water. Conclusion: In conclusion, a simple, convenient, and high-yielding catalyst-free environmentally benign method was developed for the synthesis of unsaturated amino acid esters and unsaturated amino ketones.
Keywords: β-unsaturated esters and unsaturated amino ketones